Endless Enemies : Inside FBI Counterterrorism - Holcomb, Raymond W. (Book collections on Project MUSE., 2011)
"Holcomb's memoir provides detailed information about the FBI that only a long time bureau insider can reveal such as prison conditions and interrogation techniques in Guantánamo and Afghanistan"--Jacket